An evaluation of factors affecting brand awareness in the context of social media in Malaysia - Shojaee, Somayeh; Azman, Azreen (Canadian Center of Science and Education, 2013)
Living in the middle of a global communication boom with vast usage of social media, the business environment has become more complicated. So, it is more difficult for marketers to create and increase brand awareness as they have to be able to coordinate messages and efforts across all the existing media to capture customers. Therefore, marketers have to consider these communication tools on branding process in the current competitive market-space. The purpose of this study is to evaluate the factors affecting on brand awareness through social media in Malaysia. Data for this study was obtained from 391 students of Universiti Putra Malaysia. The results indicate customer engagement, brand exposure, and electronic-word-of-mouth have positive correlation with brand awareness in the context of social media and the most effective factor is customer engagement. The study recommends that brands will be profited from social media in order to create and enhance brand awareness and the benefits will be mostly increased by using this media’s interactivity features to tie customers more closely to a brand.